Long-run labour market effects of individual sports activities - Michael Lechner (Institute for the Study of Labor (IZA), 2008)
This microeconometric study analyzes the effects of individual leisure sports participation on long-term labour market variables, on socio-demographic as well as on health and subjective well-being indicators for West Germany based on individual data from the German Socio-Economic Panel study (GSOEP) 1984 to 2006. Econometric problems due to individuals choosing their own level of sports activities are tackled by combining informative data and flexible semiparametric estimation methods with a specific way to use the panel dimension of the data. The paper shows that sports activities have sizeable positive long-term labour market effects in terms of earnings and wages, as well as positive effects on health and subjective well-being.
urn:nbn:de:101:1-2008062582
Keywords: I12; 330; Leisure sports; health; labour market; matching estimation; panel data; Freizeitverhalten; Sport; Einkommen; Gesundheit; Lebenszufriedenheit; Deutschland